2023
DOI: 10.2196/36667
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Media Data to Investigate Public Perceptions of Cannabis as a Medicine: Narrative Review

Abstract: Background The use and acceptance of medicinal cannabis is on the rise across the globe. To support the interests of public health, evidence relating to its use, effects, and safety is required to match this community demand. Web-based user-generated data are often used by researchers and public health organizations for the investigation of consumer perceptions, market forces, population behaviors, and for pharmacoepidemiology. Objective In this review,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
1
3
0
1
Order By: Relevance
“…Our research echoes previous findings that pregnant patients are using cannabis medicinally to manage pregnancy symptoms such as nausea ( 59 ). In the absence of satisfactory provider counseling, patients relied on peers for information and advice, which reiterates previous findings that individuals value information online to learn about cannabis use during pregnancy ( 62 , 63 ). Patients perceived that the maternal experience of using cannabis was pushed to the margins of the general research body, with their questions and drivers of use ignored by providers.…”
Section: Discussionsupporting
confidence: 75%
“…Our research echoes previous findings that pregnant patients are using cannabis medicinally to manage pregnancy symptoms such as nausea ( 59 ). In the absence of satisfactory provider counseling, patients relied on peers for information and advice, which reiterates previous findings that individuals value information online to learn about cannabis use during pregnancy ( 62 , 63 ). Patients perceived that the maternal experience of using cannabis was pushed to the margins of the general research body, with their questions and drivers of use ignored by providers.…”
Section: Discussionsupporting
confidence: 75%
“…Namely, conformity, experimentation, and boredom, while frequently reported by youth [2,[4][5][6], were much less often reported in this working sample. Unlike prior studies, which were mainly conducted more than 10 years ago, sleep and medical motives were also reported by almost a third of respondents, perhaps reflecting the growing public discourse on the therapeutic potential of cannabis [35,36]. A recent study conducted by our team also found that workers' compensation claimants often reported using cannabis to cope with stress and for relaxation, but those who reported using cannabis specifically for their injury and illness symptoms more often reported use for pain, sleep, and mental health [14].…”
Section: Discussionmentioning
confidence: 79%
“…Es necesario tener en cuenta que la legalización del cannabis recreativo en algunos países ha generado nuevas líneas de negocio relacionadas con la medicina, el ocio y los productos que contienen THC y CBD. Cada vez hay una mayor variedad de productos que llegan a los consumidores mediante diversas estrategias de marketing para influir en la comprensión pública de los beneficios que suponen (Krauss et al, 2017;Khademi et al, 2023), como por ejemplo alimentos, refrescos o dulces (Isorna-Folgar et al, 2022). También se difunden vídeos generados por los usuarios en plataformas promoviendo el vapeo de marihuana (Romito et al, 2015;Yang et al, 2018).…”
Section: Marco Teóricounclassified